Association Between Socio-Economic Factor, Home Sanitation, Sense of Belonging, and Health Behavior, in Patients with Dengue Hemorrhagic Fever in Kediri, East Java - Lindha Sri Kusumawati; Ambar Mudigdo; Soemanto - (Masters Program in Public Health, Sebelas Maret University, 2016)
Background: Dengue hemorrhagic fever (DHF) is an infectious disease characterized by high fever and red spots on the skin with unclear causal factor. The increasing number of DHF cases for the past few years indicated poor environmental health indicator. The purpose of this study was to determine the association between socio-economic factor, home sanitation, sense of belonging, and health behavior, in patients with DHF.Subjects and Method: This was an analytic observational study with case control design. This study was conducted at Campurejo Health Center, Kediri, East Java. A total sample of 100 patients with DHF were selected for this study. The dependent variable was health behavior. The independent variables were socio-economic factor, home sanitation, and sense of belonging. The data were collected by questionnaire and analyzed by multiple logistic regression. Results: Education ≥ senior high school (OR= 3.15; 95% CI= 1.219 to 8.140; p=0.018), family income ≥ regional minimum wage (OR= 9.143; 95% CI= 3.13 to 26.70; p=0.001), good home sanitation (OR= 3.1; 95% CI= 1.120 to 8.579; p=0.029), and sense of belonging (OR= 12.01; 95% CI= 4.021 to 35.89; p=0.001) were associated with healthier behavior.Conclusion: Education ≥ senior high school, family income ≥ regional minimum wage, good home sanitation, and sense of belonging are associated with healthier behavior.Keywords: education, family income, home sanitation, sense of belonging, health behaviorCorrespondence: Lindha Sri Kusumawati. Faculty of Health Sciences, Kadiri University. Email: lindha.sri@gmail.com.Journal of Health Promotion and Behavior (2016), 1(4): 238-243https://doi.org/10.26911/thejhpb.2016.01.04.03